Severe subcutaneous infection with Clostridium septicum in a herd of native Icelandic horses - Charlotta Oddsdóttir; Ólöf G. Sigurðardóttir; Vala Friðriksdóttir; Vilhjálmur Svansson; Birkir Þór Bragason; Sigríður Björnsdóttir (Acta Veterinaria Scandinavica)
Abstract Background Cellulitis due to infection with clostridia has not been documented in horses in Iceland. However, clostridia are well-known pathogens in Icelandic sheep, which have traditionally shared grazing land with horses. Clostridial infections of equine muscle or subcutis following injection with medicinal products have been described in other countries but have never been reported in Iceland. In this case report, we present the first documented outbreak of subcutaneous clostridial infection in horses in Iceland following subcutaneous injection. Case presentation In November 2022, 16 out of 32 horses, that some days earlier had received a subcutaneous injection of Noromectin® 1% injectable solution, developed clinical signs indicating malignant oedema. The clinical signs included pyrexia, depression, swollen limbs, chest and neck, reluctance to move and dyspnoea, leading to the death or euthanasia of five horses. In addition, one horse was found dead with no previously noted clinical signs. Necropsy of one of the five horses revealed severe, acute cellulitis in the neck region, as well as lymphadenitis in regional lymph nodes. Abscesses, some with subsequent spontaneous drainage of seropurulent material, were observed at the presumed injection site on eight surviving horses approximately 2 weeks post-injection. Bacterial culture of samples from the necropsied horse and from abscesses from three surviving horses yielded the growth of C. septicum. Analysis of water samples from the pasture where the herd was kept also revealed the presence of C. septicum. Whole genome sequencing suggested that the isolates from the diseased horses contained the same C. septicum strain, whereas the strain isolated from the water samples differed from the disease-causing isolates. Conclusions Clinical signs compatible with serious subcutaneous C. septicum infection were seen in over half of 32 horses injected with an ivermectin product, with the subsequent death of six of the horses. In the absence of other obvious sources, the outbreak suggests that C. septicum spores on the skin of these horses were introduced under the skin when they were injected. Such infections have not been reported in Iceland, although ivermectin products formulated for subcutaneous injection have been widely used for more than 30 years. The outbreak warrants further investigation into C. septicum in the environment of grazing horses in Iceland.